SOSIALISASI DAMPAK DAN PENCEGAHAN NARKOBA KEPADA SISWA SMK ASHHABUL MAIMANAH - Hamidah Hamidah; Nugrahini Kusumawati; M. Nassir Agustiawan Asnawi; Alif Fajar Ramadha; Helmalia Putri (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2023)
Drug cases are not new to the current generation of Indonesians, including in Serang Regency, especially in the Tirtayasa sub-district of Kebon Village. Not a few teenagers in Seda Kebon are plunged into the environment and drug association. This community service activity is a positive activity that aims to provide information and understanding to students about the harmful effects of drug use and how to prevent it in the community and school environment. Service activities were carried out to students of SMK class XI and XII Ashhabul Maimanah Tirtayasa District. Furthermore, students were given questionnaires, and the results were known that with this socialization activity students became more understanding about the dangers and effects of drugs. Students are also aware of the devastating effects and punishments that await when dealing with drugs. Students also understand about the influence of information from family, friends, or related institutions in raising awareness about the dangers of drugs. This conclusion was obtained from the average of students' answers to the questionnaire given by the majority gave very agreeable and affirmative responses